Psikoedukasi Mengenal Gaya Belajar Anak Sebagai Upaya Mengoptimalkan Ilmu Parenting Siswa PAUD (Pendidikan Anak Usia Dini ) - Sudiyah Anawati; Roida Eva Flora Siagian; Condro Endang Werdiningsih (CV Putra Publisher, 2025)
Early Childhood Education (PAUD) is an important stage in a child's development. Every child has a different learning style. Therefore, parents must know the types of learning styles so that they can optimize learning outcomes. Intelligence that is optimally developed through a good learning environment can lead children to become a generation of character, talent, and physical and mental health. The community service method used is a counseling approach to parents and teachers. The implementation of community service was carried out at POS PAUD Mawar 19 Sukatani, Tapos, Depok. Psychoeducational counseling to recognize learning styles in PAUD is very important to help children develop their potential optimally as well as being a source of information for teachers in determining the right learning method.